2002
DOI: 10.1007/s00421-002-0667-4
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain isoforms influence surface EMG parameters: a study of the trapezius muscle in cleaners with and without myalgia and in healthy teachers

Abstract: The present study had two aims: (1) to investigate potential differences in proportion of myosin heavy chain isoforms in the trapezius muscle between female cleaners with and without trapezius myalgia and healthy teachers, and (2) to elucidate if myosin heavy chain composition and surface electromyogram (EMG) during an isokinetic endurance test of shoulder flexors are significantly related. The subjects were divided into three groups: (1) 25 female cleaners with diagnosed work-related trapezius myalgia; (2) 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, the directions of the relationships between proportions of MyHC isoforms and MNF variables differed between the groups. Thus, in the cleaners with myalgia and the healthy teachers MNF correlated positively with the proportion of MyHC type I while in the healthy cleaners the proportion of MyHC IIA correlated positively with the two MNF variables [33]. We have no clear explanation for our finding nor to the disparity in the literature in this respect.…”
Section: Mnf and Fibre Proportionsmentioning
confidence: 46%
See 2 more Smart Citations
“…However, the directions of the relationships between proportions of MyHC isoforms and MNF variables differed between the groups. Thus, in the cleaners with myalgia and the healthy teachers MNF correlated positively with the proportion of MyHC type I while in the healthy cleaners the proportion of MyHC IIA correlated positively with the two MNF variables [33]. We have no clear explanation for our finding nor to the disparity in the literature in this respect.…”
Section: Mnf and Fibre Proportionsmentioning
confidence: 46%
“…Based on earlier results in the literature [10,21,43], it would have been reasonable to expect a negative relationship; however, in this study and in our recent study of the vastus lateralis [17] we have found a positive relationship between MNF and type I fibre type proportion. In a recent study of the trapezius of healthy cleaners, cleaners with trapezius myalgia and healthy teachers we have reported that the MyHC isoform proportions influenced the frequency content of the EMG [33]. However, the directions of the relationships between proportions of MyHC isoforms and MNF variables differed between the groups.…”
Section: Mnf and Fibre Proportionsmentioning
confidence: 84%
See 1 more Smart Citation
“…In spite of the large number of variables that influence the sEMG signal (De Luca,1997;Farina et al, 2004;Hogrel, 2005), studies on correlations between intrinsic muscle parameters and recorded signals are becoming more numerous (Gerdle et al, 1997;Karlsson & Gerdle, 2001;Kupa et al,1995;Larsson et al, 2002Larsson et al, & 2006Tygesen & Harrison, 2005). In rats, EMG parameters have been shown to be a useful tool to predict muscle excitability (Harrison & Flatman, 1999), and in sheep the technique has been used to follow postnatal muscle development (Tygesen & Harrison, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In rats, EMG parameters have been shown to be a useful tool to predict muscle excitability (Harrison & Flatman, 1999), and in sheep the technique has been used to follow postnatal muscle development (Tygesen & Harrison, 2005). sEMG recordings have also been related to the morphological state of muscles, for example i) muscle fibre composition (identified using MHC isoforms or mATPase activity)in humans (Gerdle et al, 1997;Larsson et al, 2002Larsson et al, & 2006 and in rats (Kupa et al, 1995) and, ii) muscle fibre diameter in humans (Gerdle et al, 1997;Larsson et al, 2006) and in rats (Kupa et al, 1995).…”
Section: Introductionmentioning
confidence: 99%